2019
DOI: 10.1097/jtn.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Experienced by Nurses Providing End-of-life Care in Emergency Departments in Japan

Abstract: Saving lives is the first priority in emergency departments. However, it is important to provide end-of-life care (EOLC) for patients and their families in these departments when the patient's life cannot be saved. Existing work reporting the obstacles and difficulties of nursing practice has found that the perceptions of nurses who provide EOLC include distress and conflict. The primary aims of this study were (i) to clarify the structure of the conflict experienced by nurses providing EOLC in emergency depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This study identified that non‐married nurses had a lower PC self‐competence than married nurses. Previous studies have similarly reported that single nurses experienced stronger conflicts and bear a greater emotional burden when facing difficulties during work than married nurses, owing to a lack of family support (Satake & Arao, 2019). As less experienced members of the team, it is challenging for single nurses to develop optimal patients' PC plans with other professionals and manage conflicts arising in the care of dying patients and their families.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This study identified that non‐married nurses had a lower PC self‐competence than married nurses. Previous studies have similarly reported that single nurses experienced stronger conflicts and bear a greater emotional burden when facing difficulties during work than married nurses, owing to a lack of family support (Satake & Arao, 2019). As less experienced members of the team, it is challenging for single nurses to develop optimal patients' PC plans with other professionals and manage conflicts arising in the care of dying patients and their families.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, nurses who had interactions with dying patients considered they did not have enough time to provide ongoing PC due to a heavy workload. This is a common misconception (Satake & Arao, 2019). This finding is in line with previous studies among hospice nurses (Barnett & Adams, 2020) and oncology nurses (Nguyen et al, 2014; Shen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Thus involving the nurses in the multidisciplinary decision making of EOL care will be beneficial.Nurses play a very important role in EOL care by providing family care and collaborating with the rest of the medical team. 5 Working as a nurse within the wider ICU team requires good collaborative and communication skills and few studies have focused on how we foster these skills to enhance EOL care in the ICU. Little is known about the role of nurses in end of life in the critical care setting, and therefore a grounded theory study in this area is needed to further understand this important role.…”
mentioning
confidence: 99%